(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
In the article, the problems of ensuring the employment of graduates of higher educational institutions were researched, as a conclusion of the research work, it was concluded that the mechanisms of ensuring the employment of graduates should go through the process of transformation on the basis of digital technologies.